Anthropocentric-Utilitarian Tradition and the Quest for Environmental Justice in the Niger Delta of Nigeria - Edward Uzoma Ezedike (Britain International for Academic Research (BIAR) Publisher, 2020)
There is a growing concern, lately, in the Niger Delta region, nay, Nigeria at large, over the despoliation of our environment by multinational oil companies and citizens in quest for economic gains. The problem is that humans have come to see themselves as “landlords” and masters of God’s creation rather than stewards, having untrammeled authority to plunder natural resources with reckless abandon. The resultant effect is that this unethical attitude towards the environment poses grave danger to both living and non-living things in the ecosystem and forecloses the possibilities of its sustainability. Specifically, this paper critically examines the implications of the anthropocentric- utilitarian tradition in environmental ethics for the Niger Delta region of Nigeria. The anthropocentric approach emphasizes the use of non-human natural resources solely in terms of their instrumental value to human kind. Its utilitarian dimension holds that so long as an environmental attitude or policy produces the greatest happiness, pleasure or benefit possible for the greatest number of people, it is moral. This paper posits that such tradition is quite problematic to the realization of environmental justice and wholeness in the Niger Delta. Our objective here is to show that the monumental environmental problems in the Niger Delta resulting from oil exploration are precipitated by the some unjust socio-economic and unethical principles. This paper recommends the application of the principles of environmental stewardship and environmental justice as a way out of the problem. These principles stand for moral consider ability towards the environment as well as a fair distribution of environmental burdens and benefits.